2a+3b-4c-2(3a+6b-8c)+3(4a-6c)+5a=

Simple and best practice solution for 2a+3b-4c-2(3a+6b-8c)+3(4a-6c)+5a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+3b-4c-2(3a+6b-8c)+3(4a-6c)+5a= equation:


Simplifying
2a + 3b + -4c + -2(3a + 6b + -8c) + 3(4a + -6c) + 5a = 0
2a + 3b + -4c + (3a * -2 + 6b * -2 + -8c * -2) + 3(4a + -6c) + 5a = 0
2a + 3b + -4c + (-6a + -12b + 16c) + 3(4a + -6c) + 5a = 0
2a + 3b + -4c + -6a + -12b + 16c + (4a * 3 + -6c * 3) + 5a = 0
2a + 3b + -4c + -6a + -12b + 16c + (12a + -18c) + 5a = 0

Reorder the terms:
2a + -6a + 12a + 5a + 3b + -12b + -4c + 16c + -18c = 0

Combine like terms: 2a + -6a = -4a
-4a + 12a + 5a + 3b + -12b + -4c + 16c + -18c = 0

Combine like terms: -4a + 12a = 8a
8a + 5a + 3b + -12b + -4c + 16c + -18c = 0

Combine like terms: 8a + 5a = 13a
13a + 3b + -12b + -4c + 16c + -18c = 0

Combine like terms: 3b + -12b = -9b
13a + -9b + -4c + 16c + -18c = 0

Combine like terms: -4c + 16c = 12c
13a + -9b + 12c + -18c = 0

Combine like terms: 12c + -18c = -6c
13a + -9b + -6c = 0

Solving
13a + -9b + -6c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9b' to each side of the equation.
13a + -9b + 9b + -6c = 0 + 9b

Combine like terms: -9b + 9b = 0
13a + 0 + -6c = 0 + 9b
13a + -6c = 0 + 9b
Remove the zero:
13a + -6c = 9b

Add '6c' to each side of the equation.
13a + -6c + 6c = 9b + 6c

Combine like terms: -6c + 6c = 0
13a + 0 = 9b + 6c
13a = 9b + 6c

Divide each side by '13'.
a = 0.6923076923b + 0.4615384615c

Simplifying
a = 0.6923076923b + 0.4615384615c

See similar equations:

| (x^10)=77 | | 5/10=1/q | | 2x+75=6x+1 | | 3/4=q/8 | | 1/2t=9=25 | | 4/10=q/5 | | -10r=-3r+56 | | 82=4u+10 | | 20=12-4z | | -5(3u-6)+4u=7(u+4) | | 3*0+2=0-2 | | 3/6=q/12 | | 7xy-4y= | | 64X+49Y-3136=0 | | m-4/3=-3 | | x+3y^3= | | Y^2-x^2+6x-4y=6 | | -13+4x+6=37 | | -5x-1=3x-1 | | 6x-3(-33/204)=48 | | 5/6x1/2=1/3 | | 9(9-k)=6k-1 | | 10-32=12 | | 2(x+14)=3x+14 | | 204/x=48 | | 10+0b=550 | | -7x^3=-7 | | -4-4x=x^2 | | (x-(4-7i))(x+(4-7i))=0 | | 5/3x=1,400 | | 5/3x=2004 | | 3(x-2)=10+x-2 |

Equations solver categories